The Lung Macrophage in SARS-CoV-2 Infection: A Friend or a Foe? - Abassi, Zaid; Knaney, Yara; Karram, Tony; Heyman, Samuel N. (Frontiers in Immunology, 2020)
Respiratory, circulatory, and renal failure are among the gravest features of COVID-19 and are associated with a very high mortality rate. A common denominator of all affected organs is the expression of angiotensin-converting enzyme 2 (ACE2), a protease responsible for the conversion of Angiotensin 1-8 (Ang II) to Angiotensin 1-7 (Ang 1-7). Ang 1-7 acts on these tissues and in other target organs via Mas receptor (MasR), where it exerts beneficial effects, including vasodilation and suppression of inflammation and fibrosis, along an attenuation of cardiac and vascular remodeling. Unfortunately, ACE2 also serves as the binding receptor of SARS viral spike glycoprotein, enabling its attachment to host cells, with subsequent viral internalization and replication. Although numerous reports have linked the devastating organ injuries to viral homing and attachment to organ-specific cells widely expressing ACE2, little attention has been given to ACE-2 expressed by the immune system. Herein we outline potential adverse effects of SARS-CoV2 on macrophages and dendritic cells, key cells of the immune system expressing ACE2. Specifically, we propose a new hypothesis that, while macrophages play an important role in antiviral defense mechanisms, in the case of SARS-CoV, they may also serve as a Trojan horse, enabling viral anchoring specifically within the pulmonary parenchyma. It is tempting to assume that diverse expression of ACE2 in macrophages among individuals might govern the severity of SARS-CoV-2 infection. Moreover, reallocation of viral-containing macrophages migrating out of the lung to other tissues is theoretically plausible in the context of viral spread with the involvement of other organs.